Development of a food frequency questionnaire based on the evaluation of the habitual dietary intake of patients with Non-alcoholic Fatty Liver Disease (Research, Society and Development, 2021)
Objective: to evaluate the usual food intake of patients with Non-alcoholic Fatty Liver Disease (NAFLD) according to the degree of hepatic steatosis, to verify the association with anthropometric variables and to develop a Food Frequency Questionnaire (FFQ) targeted at this population. Methods: Observational cross-sectional study developed with 60 adult patients diagnosed with mild or moderate NAFLD. Anthropometric evaluation and 24-hour recall were performed. For the analysis of the diet composition and food classification, the NOVA proposal was considered. For the development of FFQ, foods that contributed up to 95% of energy, macronutrients and micronutrients of interest were selected. The Mann Whithey test was used to verify the difference between the medians of the variables with the grade of hepatic steatosis and the Spearman correlation coefficient for the calculation of correlations. The significance level adopted in the test decision was 5%. Results: similar dietary intake was observed among patients with NAFLD, with predominance of natural or minimally processed foods. The degree of food processing did not present significant correlation with anthropometric measurements and steatosis degree. The FFQ was prepared from the selection of 96 foods. Conclusions: food consumption is like the basic pattern of the Brazilian population. The total intake of macro and micronutrients of these patients did not correlate with the severity of steatosis, nor with anthropometric data. The proposed FFQ is expected to become a useful tool in monitoring dietary practices of individuals with NAFLD.